Wavelength-induced polarization bistability in 1550 nm VCSELs subject to orthogonal optical injection - Torre, Maria Susana (2010)
We report on a theoretical and experimental investigation of the bistable behavior of the polarization of longwavelength single-transverse mode vertical-cavity surface-emitting lasers (VCSELs) when subject to orthogonal optical injection. We have studied the bistability properties of the polarization switching that appear when changing the master laser wavelength with a fixed master laser power. Two bistable regions are found for polarization switchings appearing at short and long wavelengths. The directions of the obtained hysteresis cycles are in agreement with the experimental results. The widths of both bistable regions are also found to be similar and nearly independent of the injected power. The width of the region where polarization switching takes place is shown to increase as the injected power is increased. A good overall qualitative agreement is found between our theoretical and experimental results.